1972
DOI: 10.1002/qua.560060215
|View full text |Cite
|
Sign up to set email alerts
|

The generalized separated electron pair model. III. An application to three localization schemes for CO

Abstract: AbstractsThe separated electron pair (SEP) model (strongly orthogonal geminals) and methods for its systematic extension have been applied to three different localization schemes for C-0.The optimum SEP wave function is obtained for the particular localization scheme that involves three equivalent bent bonds. The major corrections to the SEP model arise from one-electron transfer terms. Two-electron transfer terms were important only for those pairs that were not well localized. I t was found that the separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[2][3][4][5][6][7] Sometimes this model is referred to as separated electron pair ͑SEP͒ theory. [8][9][10][11][12] Most prior studies focused on the total amount of correlation energy recovered by the product of strongly orthogonal geminals. It was generally concluded that the model has its limitations, primarily attributable to either lack of intergeminal correlation, 5 strong orthogonality approximation, 13 or both.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Sometimes this model is referred to as separated electron pair ͑SEP͒ theory. [8][9][10][11][12] Most prior studies focused on the total amount of correlation energy recovered by the product of strongly orthogonal geminals. It was generally concluded that the model has its limitations, primarily attributable to either lack of intergeminal correlation, 5 strong orthogonality approximation, 13 or both.…”
Section: Introductionmentioning
confidence: 99%